Manufacturing method for nonaqueous secondary battery
The method addresses the variability in SEI coating thickness due to changes in the negative electrode surface area by adjusting the concentration of additives in the electrolyte, ensuring consistent battery performance.
Patent Information
- Application Number
- JP2023156116
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
The thickness of the solid electrolyte interface (SEI) coating on the negative electrode of nonaqueous secondary batteries can vary due to changes in the surface area of the negative electrode mixture layer during manufacturing, affecting battery performance.
A manufacturing method for nonaqueous secondary batteries that involves using a nonaqueous electrolyte with a first additive containing boron and a second additive that forms a coating on the first additive-derived coating, with the concentration of the second additive adjusted based on the surface area of the negative electrode mixture layer to maintain uniform coating thickness.
This method ensures uniform thickness of the SEI coating, thereby maintaining good battery performance and suppressing variations caused by changes in the surface area of the negative electrode mixture layer.
Smart Images

Figure 2025047564000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a non-aqueous secondary battery. [Background technology]
[0002] In non-aqueous secondary batteries such as lithium ion secondary batteries, a solid electrolyte interface (SEI) coating is formed on the surface of the negative electrode mixture layer. The SEI coating (hereinafter simply referred to as the coating) suppresses decomposition of the electrolyte during the use of the battery.
[0003] The coating is formed during the initial charging process after the non-aqueous secondary battery is assembled. The coating is derived from compounds contained in the electrolyte. The thickness of the coating affects the battery performance. That is, if the coating is excessively thin, the battery resistance of the non-aqueous secondary battery decreases, while the effect of suppressing the decomposition of the non-aqueous electrolyte decreases. If the coating is excessively thick, the suppression effect of the electrolyte increases, while the battery resistance increases.
[0004] The thickness of the coating depends on the amount of the compound contained in the electrolyte that forms the coating, and on the surface area of the negative electrode mixture layer. 2 / g or more 5.0m 2 / g or less, and the amount of LiBOB skeleton component is 4.3 μmol / m 2 The above non-aqueous electrolyte secondary batteries have been proposed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-106250 A Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, the surface area of the negative electrode mixture layer on which the coating is formed may change depending on the conditions during the manufacture of the negative electrode plate even if the composition of the negative electrode mixture layer does not change. When the composition of the electrolyte is constant, the coating formed on the negative electrode mixture layer becomes thinner as the surface area of the negative electrode mixture layer increases, and the coating formed on the negative electrode mixture layer becomes thicker as the surface area of the negative electrode mixture layer decreases. As described above, the thickness of the coating affects the battery performance, so it is desirable to control the thickness of the coating within an appropriate range even if the manufacturing conditions change depending on the manufacturing lot, etc. [Means for solving the problem]
[0007] A method for manufacturing a nonaqueous secondary battery that solves the above-mentioned problems is a method for manufacturing a nonaqueous secondary battery comprising a positive electrode plate having a positive electrode mixture layer, a negative electrode plate having a negative electrode mixture layer, and a nonaqueous electrolyte, the nonaqueous electrolyte including a film-forming material that forms a film on the negative electrode mixture layer, the film-forming material including a first additive that contains boron and forms a film on the surface of the negative electrode mixture layer, and a second additive that forms a film on the film derived from the first additive, the method including: setting a target value for the amount of film of the second additive per unit area of the negative electrode mixture layer; measuring a surface area of the negative electrode mixture layer; and setting a constant concentration of the second additive regardless of the surface area. A non-aqueous electrolyte solution containing the first additive and the second additive, the concentration of which is adjusted based on the surface area so that the target value is reached when all of the second additive is laminated as a coating, is prepared, and an initial charging step is performed to charge the non-aqueous secondary battery into which the non-aqueous electrolyte solution has been injected, the initial charging step including a first step of holding the coating derived from the first additive at an oxidation-reduction potential at which a coating derived from the first additive is generated in the negative electrode mixture layer for a certain period of time to generate a coating derived from the first additive, and a second step of further performing charging to generate a coating derived from the second additive to be laminated on the coating derived from the first additive.
[0008] When the time of holding the oxidation-reduction potential at which the film is generated in the initial charging step is constant, the thickness of the film derived from the first additive changes depending on the concentration of the first additive in the electrolyte. In addition, the second additive generates a film derived from the second additive on the film derived from the first additive, while the first additive does not generate a film on the film derived from the second additive. According to the above method, the concentration of the first additive is constant regardless of the surface area of the negative electrode mixture layer. Therefore, the thickness of the film derived from the first additive can be made uniform. In addition, the concentration of the second additive is adjusted according to the surface area of the negative electrode mixture layer. Furthermore, since the second step of generating a film derived from the second additive is performed after the first step of generating a film derived from the first additive, the film derived from the first additive does not grow during or after the second step. Therefore, even when the surface area of the negative electrode mixture layer changes in the manufacturing process of the negative electrode plate, the thickness of the film formed on the negative electrode can be made uniform.
[0009] In the method for producing a nonaqueous secondary battery, it is preferable that a redox potential at which a film derived from the second additive is formed is lower than a redox potential at which a film derived from the first additive is formed.
[0010] In the above method for producing a nonaqueous secondary battery, it is preferable that the time for which the oxidation-reduction potential is maintained to produce the coating derived from the first additive is less than 7 seconds. In the method for producing the nonaqueous secondary battery, the first additive is a lithium metal standard (vs. Li / Li + ) the oxidation-reduction potential is preferably 1.2 V or more. Effect of the Invention
[0011] According to the present invention, the thickness of the coating formed on the negative electrode can be made uniform, thereby making it possible to suppress variation in battery performance while maintaining good battery performance. [Brief description of the drawings]
[0012] [Figure 1] 1A to 1C are diagrams showing an electrode assembly according to an embodiment of a method for manufacturing a nonaqueous secondary battery. [Diagram 2] 5A to 5C are diagrams for explaining a coating production process in the embodiment; [Diagram 3] 4A to 4C are diagrams illustrating a design procedure for a nonaqueous secondary battery in the embodiment. [Figure 4] 3A to 3C are diagrams illustrating a procedure for producing a nonaqueous secondary battery in the embodiment. [Diagram 5] 1 is a graph showing the resistance ratio versus negative electrode surface area for an example in which the LiBOB concentration was not adjusted and an example in which the LiBOB concentration was adjusted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An embodiment of a method for producing a non-aqueous secondary battery will be described with reference to Figures 1 to 4. In this embodiment, the non-aqueous secondary battery using a non-aqueous electrolyte solution will be described as a lithium-ion secondary battery. The lithium-ion secondary battery is mounted on an electric vehicle or a hybrid vehicle and supplies power to an electric motor or the like.
[0014] [Lithium-ion secondary battery] 1 shows an electrode assembly 20 of a lithium ion secondary battery 10 (hereinafter simply referred to as battery 10). The electrode assembly 20 is housed in a case (not shown) together with a nonaqueous electrolyte (hereinafter simply referred to as electrolyte). The electrode assembly 20 is a flat wound body formed by winding a laminate in which a long positive electrode plate 21 and a negative electrode plate 24 are stacked with a separator 27 between them.
[0015] [Positive plate] The positive electrode plate 21 will be described. The positive electrode plate 21 includes a positive electrode substrate 22 and a positive electrode mixture layer 23. The positive electrode substrate 22 is a long, sheet-like member. The positive electrode mixture layer 23 is provided on each of two surfaces of the positive electrode substrate 22 that face in opposite directions.
[0016] The positive electrode substrate 22 is made of, for example, a metal foil. The metal foil is made of aluminum or an alloy mainly composed of aluminum. The positive electrode mixture layer 23 includes a positive electrode active material, a conductive material, and a binding material (binder). As the positive electrode active material in this embodiment, one or more of various materials known to be usable as a positive electrode active material contributing to a battery reaction can be used. As a suitable example, the positive electrode active material is a lithium composite metal oxide such as a layered system or a spinel system (e.g., LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of the conductive material include carbon black such as acetylene black and ketjen black, and other powdered carbon materials (such as graphite). Examples of the binder include polyvinylidene fluoride (PVDF), styrene butadiene copolymer (SBR), polytetrafluoroethylene (PTFE), and the like. The positive electrode binder is a resin component, and at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), and styrene butadiene rubber (SBR) can be used.
[0017] [Negative plate] The negative electrode plate 24 includes a negative electrode substrate 25 and a negative electrode composite layer 26. The negative electrode substrate 25 is a long, sheet-like member. The negative electrode substrate 25 is, for example, a metal foil made of copper or an alloy mainly composed of copper.
[0018] The negative electrode mixture layer includes a negative electrode active material, a negative electrode conductive agent, a negative electrode thickener, and a negative electrode binder. The negative electrode active material is a material capable of absorbing and releasing lithium ions. As the negative electrode active material of the present embodiment, one or more of various materials known to be usable as a negative electrode active material can be used. As a suitable example, the negative electrode active material is made of a carbon-based material. Examples of the carbon-based material include graphite, non-graphitizable carbon, easily graphitizable carbon, and carbon nanotubes. The negative electrode active material may be a composite particle in which graphite particles are coated with an amorphous carbon layer. For example, the negative electrode conductive agent may be the same as the conductive agent of the positive electrode. For example, carboxymethyl cellulose (CMC) can be used as the negative electrode thickener. The negative electrode binder is at least one selected from the group consisting of PVDF, PVA, and SBR.
[0019] [Separator] The separator 27 prevents contact between the positive electrode plate 21 and the negative electrode plate 24, and retains the electrolyte between the positive electrode plate 21 and the negative electrode plate 24. The separator 27 is a nonwoven fabric made of polypropylene or the like. As the separator 27, for example, a porous polymer membrane such as a porous polyethylene membrane, a porous polyolefin membrane, or a porous polyvinyl chloride membrane, an ion-conductive polymer electrolyte membrane, or the like can be used.
[0020] [Electrolyte] The electrolyte is a composition in which a supporting salt is contained in a non-aqueous solvent. The non-aqueous solvent may be, for example, one or more materials selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. The supporting salt may be, for example, one or more lithium compounds (lithium salts) selected from LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC4F9SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiI, etc.
[0021] The electrolytic solution further contains an additive that forms an SEI film (hereinafter, simply referred to as a film). The additive as a film-forming material includes a first additive and a second additive. The first additive preferably has a redox potential higher than that of the second additive. The redox potential of the first additive is based on lithium metal (vs. Li / Li + ) is preferably 1.2 V or more.
[0022] The first additive is a compound containing B (boron). For example, the first additive is lithium bis(oxalato)borate (LiBOB, LiB(C2O4)2), which is an example of a lithium salt. In addition to or instead of LiBOB, LiBF4, LiFOB, etc. may be used as the first additive. For example, when the first additive is LiBOB, LiBOB is added to the electrolyte so that the concentration of LiBOB is 0.001 mol / L or more and 0.1 mol / L or less. The coating derived from the first additive is hereinafter referred to as the first coating.
[0023] The second additive is other than the first additive and is a material for a coating that can be laminated on the first coating. The second additive is an inorganic compound containing S (sulfur) or P (phosphorus) or an organic compound having various functional groups. For example, the second additive can be one or more of lithium fluorosulfate, lithium difluorophosphate, linear sulfone-based compounds, cyclic sulfone-based compounds, linear / cyclic compounds having an isocyanate group, propionate-based compounds, unsaturated cyclic carbonates, fluorinated unsaturated cyclic carbonates, and methylene bissulfonate derivatives. The coating derived from the second additive is hereinafter referred to as the second coating. In other words, the second coating can be formed on the first coating.
[0024] [Coating formation process] The process of forming the coating will be described with reference to Fig. 2. After the battery 10 is assembled, the electrolyte is poured into the case. Immediately after the electrolyte 30 is poured, the coating derived from the first additive 31 and the second additive 32 is not formed on the negative electrode mixture layer 26. The first additive 31 and the second additive 32 are contained in the electrolyte 30 in a state of being dissolved in a non-aqueous solvent (before the coating is formed).
[0025] Before the shipment of the battery 10, a conditioning process (initial charging process) for charging the battery 10 is performed. In the conditioning process, a film is formed on the negative electrode composite material layer 26 by initial charging. As the charge amount of the battery 10 increases, the positive electrode potential rises and the negative electrode potential drops. Therefore, at the initial stage of the conditioning process, first, due to the decomposition of the first additive 31 with a high oxidation-reduction potential, the first film 41 derived from the first additive 31 is generated on the surface of the negative electrode active material particles (generation of the first film).
[0026] By maintaining the battery voltage so that the negative electrode potential becomes the oxidation-reduction potential V1 at which the first film 41 is generated, the first film 41 grows. At this time, since the oxidation-reduction potential V2 of the second additive is lower than the oxidation-reduction potential V1 of the first additive (V2 < V1), the second film is not generated when the negative electrode potential is maintained at the oxidation-reduction potential V1.
[0027] Also, the inventors have found that when the holding time, which is the time during which the negative electrode potential is maintained at the oxidation-reduction potential V1, is short, the thickness of the first film 41 becomes almost constant depending on the concentration of the first additive 31 regardless of the surface area of the negative electrode composite material layer 26. However, it is a prerequisite that the electrolytic solution 30 contains sufficient first additive 31 to form a first film 41 with a uniform thickness on the negative electrode composite material layer 26. The thickness of the generated film can be estimated by the DC resistance, impedance, etc. of the battery 10. Therefore, in order to make the thickness of the first film 41 uniform, the concentration of the first additive in the electrolytic solution 30 is made constant.
[0028] Furthermore, by setting the negative electrode potential to be equal to or lower than the oxidation-reduction potential V2 in the conditioning process, the second film 42 derived from the second additive 32 is generated on the first film 41 (generation of the second film). The second film 42 contains decomposition products of the second additive 32. When the electrolytic solution 30 contains a plurality of types of second additives 32, the "oxidation-reduction potential V2" may correspond to a plurality of different potentials corresponding to each of the second additives 32. Thereby, a film 40 including the first film 41 and the second film 42 is generated.
[0029] The inventors have found that after the second coating 42 has grown, a coating derived from the first additive is not formed even if the negative electrode potential is equal to or lower than the oxidation-reduction potential V1 of the first additive. As described above, the thickness of the first coating 41 is almost constant depending on the concentration of the first additive 31 regardless of the surface area of the negative electrode mixture layer 26, whereas the thickness of the second coating 42 varies depending on the surface area of the negative electrode mixture layer 26. For this reason, in order to make the thickness of the second coating 42 uniform, it is necessary to adjust the concentration (addition amount) of the second additive 32 depending on the surface area of the negative electrode mixture layer 26. That is, the concentration of the second additive 32 is increased when the surface area of the negative electrode mixture layer 26 is relatively large, and is decreased when the surface area of the negative electrode mixture layer 26 is relatively large.
[0030] [Method of manufacturing non-aqueous secondary battery] A manufacturing method including a design procedure for the battery 10 and a fabrication procedure for the battery 10 will be described with reference to FIGS.
[0031] The design procedure for the battery 10 will be described with reference to FIG. 3. First, a target value for the coating amount per unit area of the second coating 42 is set (step S1). The coating amount per unit area of the second coating 42 corresponds to the thickness of the second coating 42. The target value can be set through experiments or the like. There is no particular limitation on the method for determining the target value, but for example, 2 ) are known, a plurality of samples of the battery 10 are prepared. Then, an electrolyte solution 30 in which the concentration of the first additive 31 is constant and the concentration of the second additive 32 is changed is injected into each sample. A conditioning process is performed on each sample to form a coating 40 on the negative electrode of each sample. Furthermore, a sample having suitable battery performance is identified by evaluating the battery performance of each sample. The battery performance to be evaluated is the degree of decomposition of the electrolyte solution 30, the internal resistance of the battery 10, etc. Assuming that the entire amount of the second additive 32 becomes the second coating 42 by taking a sufficient amount of time for charging, the amount of the second additive 32 added in the electrolyte solution 30 of the identified sample is divided by the surface area of the negative electrode mixture layer 26 to obtain a target value of the coating amount per unit area. The target value may be a constant value or a suitable range.
[0032] The target value for the amount of coating per unit area is constant regardless of the surface area of the negative electrode composite layer 26, but it is preferable to set a new value when it is expected that the composition of the second coating 42 will change significantly, such as when the material used for the second additive 32 is changed, or when the materials contained in the negative electrode composite layer 26 and their ratio are changed.
[0033] Next, the surface area of the negative electrode mixture layer 26 is identified (step S2). Cases where a change in the surface area is estimated include cases where various measured values monitored in the manufacturing process of the negative electrode plate 24 change, where the manufacturing lot of each material contained in the negative electrode mixture layer 26 is changed, and the like. The surface area may be identified by sampling inspection of the negative electrode plate 24 at regular intervals or for each manufacturing lot to be inspected, or may be identified when a change in the surface area of the negative electrode mixture layer 26 is particularly estimated.
[0034] The surface area is determined using the weight of the negative electrode mixture on the negative electrode substrate 25, the coating area of the negative electrode mixture on the negative electrode substrate 25, and the BET specific surface area of the negative electrode mixture layer 26. The weight of the negative electrode mixture layer 26 is the weight of the negative electrode mixture layer 26 per unit area of the negative electrode substrate 25, and is expressed in units of, for example, "mg / cm 2 ". The coating area of the negative electrode composite is the area of the negative electrode substrate 25 coated with the negative electrode composite paste, which is the precursor of the negative electrode composite layer 26. The BET specific surface area can be measured by a method known as a method for measuring the BET specific surface area, such as a method conforming to "JIS Z8830 Measurement of Specific Surface Area of Powder (Solid) by Gas Adsorption" or "ISO 9277:2022 Measurement of Specific Surface Area of Solid by Gas Absorption-BET Method". The specific surface area is the surface area of a sample divided by its mass, and is expressed in units of, for example, "m 2 / g". Surface area can be calculated by multiplying the basis weight, coated area, and BET specific surface area after adjusting the units (surface area = "basis weight" - "coated area" - "BET specific surface area").
[0035] Next, the concentration of the additives in the electrolytic solution 30 is set (step S3). The amounts of the non-aqueous solvent and supporting salt are constant. The concentration of the first additive 31 is constant, while the concentration of the second additive 32 is determined according to the surface area determined in step S2. As the concentration of the first additive 31 in the electrolytic solution 30 increases, the first coating 41 becomes thicker, so a concentration that will give a suitable thickness for a predetermined retention time is determined in advance.
[0036] Moreover, the amount (concentration) of second additive 32 to be added is determined by multiplying the target value of the coating amount per unit area set in step S1 by the surface area of negative electrode mixture layer 26 specified in step S2.
[0037] 4, the procedure for producing the battery 10 will be described. The procedures for producing the positive electrode plate 21, the negative electrode plate 24, and the electrolyte 30 will be omitted. The amounts of the first additive 31 and the second additive 32 added to the electrolyte 30 are adjusted so that the electrolyte 30 has the concentration set in step S3.
[0038] The battery 10 is assembled using the prepared positive electrode plate 21, negative electrode plate 24, etc. (Step S10). Specifically, the positive electrode plate 21, negative electrode plate 24, and separator 27 are wound to prepare the electrode body 20, and the electrode body 20 is housed in a case and sealed with a lid or the like. A positive electrode terminal is electrically connected to the positive electrode plate 21, and a negative electrode terminal is electrically connected to the negative electrode plate 24. Then, an electrolyte 30 is poured into the case.
[0039] Next, the first step included in the conditioning step (initial charging step) is performed (step S11). In the first step, the battery voltage is maintained for a certain holding time at a voltage that causes the negative electrode potential to be the oxidation-reduction potential V1. In order to shorten the conditioning step, the holding time is preferably less than 7 seconds.
[0040] In the first step, a first coating 41 of a substantially constant thickness is formed on the negative electrode mixture layer 26. The coating 40 captures lithium ions during the formation process, and when the first additive 31 is LiBOB, lithium ions are generated by the decomposition of the first additive 31, and the lithium ions can participate in the battery reaction.
[0041] After the first step, the second step of the conditioning process is performed (step S12). The second step is a step of charging the battery 10 up to a predetermined battery voltage. At this time, the charging method is not particularly limited as long as the second coating 42 is produced.
[0042] In the second step, second coating 42 is formed on first coating 41. Since the concentration of second additive 32 is adjusted according to the surface area of negative electrode mixture layer 26, second coating 42 is formed uniformly.
[0043] After the conditioning step is completed, an aging step is performed (step S13). In the aging step, the battery 10 that has reached a predetermined state of charge (SOC) is discharged under predetermined conditions to exclude abnormal batteries.
[0044] 5 is a graph showing the resistance ratios of batteries 10A-10C in which the concentration of first additive 31 in electrolyte 30 is constant, and batteries 50A-50C in which the concentration of first additive 31 is increased to compensate for a smaller amount of electrolyte injected than batteries 10A-10C, thereby adjusting the total amount of the first additive per surface area of negative electrode mixture layer 26. The horizontal axis shows the surface area of negative electrode mixture layer 26. The vertical axis shows the ratio of DC resistance of each of batteries 10B, 10C, and 50A-50C when the DC resistance of battery 10A is set to "100%."
[0045] The surface area of negative electrode mixture layer 26 of batteries 10A to 10C and batteries 50A to 50C is 80 m 2 More than 90m 2 This is within the following preferred range: The resistance ratios of the batteries 10B and 10C are 101% and 96%, respectively. That is, in the graph of FIG. 5, the difference in the resistance ratios of the batteries 10A to 10C is within 5%.
[0046] On the other hand, the concentration of the first additive 31 in the electrolyte solution 30 contained in the batteries 50A to 50C is made higher than that of the batteries 10A to 10C. Specifically, in consideration of the smaller amount of electrolyte injected in the batteries 50A to 50C, the concentration of the first additive 31 was adjusted so that the "amount of electrolyte injected × concentration of the first additive 31 ÷ surface area (S1) of the negative electrode mixture layer 26" was equivalent to that of the battery 10A.
[0047] The resistance ratios of batteries 50A to 50C are 114%, 108%, and 106%, respectively, which are higher than the resistance ratios of batteries 10A to 10C. In addition, in the graph of Fig. 5, the difference in the resistance ratios of batteries 50A to 50C is within 8%. In other words, when the concentration of first additive 31 is constant, the thickness of first coating 41 is more uniform than when the concentration is changed according to the surface area of negative electrode mixture layer 26.
[0048] As described above, according to the embodiment, the following effects can be obtained. (1) When the time for which the first coating 41 is held at the oxidation-reduction potential at which the first coating 41 is formed in the conditioning step is short and constant, the thickness of the first coating 41 changes depending on the concentration of the first additive 31 in the electrolytic solution 30. In addition, the second additive 32 contained in the electrolytic solution 30 forms the second coating 42 derived from the second additive 32 on the first coating 41 derived from the first additive 31, while the first additive 31 does not form the first coating 41 on the second coating 42. According to the above embodiment, the concentration of the first additive 31 is constant regardless of the surface area of the negative electrode mixture layer 26. Therefore, the thickness of the first coating 41 can be made uniform. In addition, the concentration of the second additive 32 is adjusted according to the surface area of the negative electrode mixture layer 26. Furthermore, since the second step of forming the second coating 42 is performed after the first step of forming the first coating 41, the first coating 41 does not grow during or after the second step. Therefore, even if the surface area of the negative electrode mixture layer 26 changes in the manufacturing process of the negative electrode plate 24, the thickness of the coating 40 consisting of the first coating 41 and the second coating 42 can be made uniform. Therefore, good battery performance can be maintained while suppressing its variation.
[0049] (2) The first additive 31 and the second additive 32 were selected so that the redox potential at which the second coating 42 is formed is lower than the redox potential at which the first coating 41 is formed. According to this, when charging the battery 10 in the conditioning step, the first coating 41 is first formed by holding for a certain period of time at the redox potential at which the first coating 41 is formed, and then charging is performed to form the second coating 42.
[0050] (3) The time for which the oxidation-reduction potential is maintained for forming the first film 41 is set to less than 7 seconds, which makes it possible to shorten the conditioning step. (4) The first additive 31 is based on lithium metal (vs. Li / Li + ) the oxidation-reduction potential is set to be 1.2 V or more. This makes it easier for the first coating 41 to be formed before the second coating 42 is formed.
[0051] Each of the above-described embodiments can be modified as follows. The nonaqueous secondary battery of the above embodiment has an electrode structure in which a positive electrode plate and a negative electrode plate are wound with a separator interposed therebetween. Alternatively, the lithium secondary battery may be, for example, a stacked battery in which a plurality of positive electrode plates and a plurality of negative electrode plates are alternately stacked with a separator interposed therebetween. Also, instead of the square battery 10, the lithium secondary battery may be a button battery.
[0052] In the above embodiment, the nonaqueous secondary battery is mounted on an electric vehicle or a hybrid vehicle and supplies power to an electric motor, etc. Alternatively, the lithium ion secondary battery may be used as a power source for small devices such as a mobile phone terminal, or as a power source for other devices such as moving objects other than automobiles, such as motorcycles and ships.
[0053] In the above embodiment, the nonaqueous secondary battery is a lithium ion secondary battery, but the nonaqueous secondary battery may be another type of battery, such as a sodium ion battery. [Explanation of symbols]
[0054] 10...Lithium-ion secondary battery 21…Positive electrode plate 22...Negative electrode plate 41...First coating 42…Second coating
Claims
1. A method for manufacturing a non-aqueous secondary battery including a positive electrode plate having a positive electrode mixture layer, a negative electrode plate having a negative electrode mixture layer, and a non-aqueous electrolyte solution, comprising: the nonaqueous electrolyte solution contains a coating material that forms a coating on the negative electrode mixture layer, the coating material includes a first additive that contains boron and forms a coating on a surface of the negative electrode mixture layer, and a second additive that forms a coating on the coating derived from the first additive, A target value of a coating amount per unit area of the negative electrode mixture layer is set for the second additive; Measure the surface area of the negative electrode mixture layer; preparing the nonaqueous electrolyte solution including the first additive having a constant concentration regardless of the surface area and the second additive having a concentration adjusted based on the surface area so that the second additive has the target value when the entire second additive is laminated as a coating; An initial charging step is performed to charge the nonaqueous secondary battery into which the nonaqueous electrolyte solution has been injected; The initial charging step includes a first step of holding for a certain period of time at an oxidation-reduction potential at which a film derived from the first additive is generated in the negative electrode mixture layer to generate a film derived from the first additive, and a second step of further performing charging to generate a film derived from the second additive that is laminated on the film derived from the first additive.
2. The method for producing a nonaqueous secondary battery according to claim 1 , wherein an oxidation-reduction potential at which the coating derived from the second additive is formed is lower than an oxidation-reduction potential at which the coating derived from the first additive is formed.
3. The method for producing a nonaqueous secondary battery according to claim 1 , wherein the time for which the oxidation-reduction potential is maintained to produce the coating derived from the first additive is less than 7 seconds.
4. The first additive is a lithium metal standard (vs. Li / Li + 2. The method for producing a nonaqueous secondary battery according to claim 1, wherein the oxidation-reduction potential of the nonaqueous electrolyte is 1.2 V or more relative to the aqueous solution.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2019106250A